Different Age Marriage Yaman: Study Of Muslim Man's Marriage To Woman Of The Book - Nurmu’izzatin Zaharatul Parhi (ASTEEC, 2024)
In writing this article, I would like to fully elaborate on the Yemeni laws regarding the marriage of Muslim women in Yemen, discussing the annulment of marriages of men who adhere to Islam or Muslims who do not marry Muslim women and women of the Book in Yemen. As for the women of the book who can be married to Muslim men in Yemen, it is necessary to elaborate on the permissibility of marrying women who are not Muslims. Yemen itself fully takes the source of law in the text of the Quran where the regulation of marriage in Yemen between Muslim men and women of the book is allowed and regulated in Yemeni legal laws. On the other hand, interfaith marriages in other regions regarding women of the book cannot be found, in Indonesia for example, interfaith marriages only explain marriages between Muslims and non-Muslims or non-Muslims, there is no mention of women of the book at all. For this reason, this article aims to elaborate on the explanation of women of the book, in the midst of the debate whether or not it is permissible to marry a woman of the book, Yemen still adheres to the text of the Quran which allows Muslim men to marry women of the book to this day.